إعادة تأهيل و توظيف البرج العسكري كافاريللي بمدينة الجلفة - براهيمي, رحمة; Hebboul, Hanane, Directeur de thèse (My University, 2020)
By highlighting new preservation concepts, there are several conservation processes for historic monuments. Among these methods is the reuse of a historic monument for purposes other than that for which it was built. Our research work is carried out within this framework. The goal of this work is to divert the Tower-El-Askari located in the city of Djelfa from its military use for a completely different use while preserving its historical and architectural character. For this, we based our work on the diversion of the use of monuments on the method used in the two examples we studied. The aim is to give the El-Askari Tower a modern function that is more attractive to the public. Due to its architectural specificities and its construction style (construction materials and techniques) as well as the structural condition of the building and its capacity to receive new uses, we have studied the spaces and made structural adjustments for a better functional rehabilitation. . Taking into account the architectural features and the structural adjustments we made, we decided to transform this building into a shopping center
Laghouat : Université Amar Telidji - Département d'architecture Option : patrimoine